SYSTEM USABILITY EVALUATION OF THE DIGITAL AUTOMATIC WEATHER SYSTEM AT BMKG LAMPUNG PROVINCE - Rintiana, Rintiana; Triloka, Joko (IJISCS (International Journal of Information System and Computer Science), 2025)
The Digital Automatic Weather System (AWS) is a vital tool for real-time meteorological data collection, utilized by the Indonesian Agency for Meteorology, Climatology, and Geophysics (BMKG) to support weather monitoring activities. However, the effectiveness of this technology largely depends on its perceived usability among users. This study aims to evaluate the usability level of the Digital AWS implemented at BMKG Lampung Province by applying the System Usability Scale (SUS) method. Data were collected through SUS questionnaires completed by AWS users within the BMKG environment. The analysis revealed an average SUS score of 59.9, which falls into the Marginal Low category and below the industry standard benchmark of 68. These findings suggest that, although the Digital AWS is functional, several aspects require improvement, particularly in interaction simplicity, interface consistency, and usage efficiency. Recommendations are directed toward enhancing interface design, simplifying navigation, and providing user training to ensure that the Digital AWS can optimally support BMKG’s operational activities.